Strategies of Hospital Marketing for Increasing Patient Satisfaction: A Systematic Review - Sari, Lenggo Geni (UI Scholars Hub, 2020)
Patient satisfaction is the most important of hospital goal. The hospital who has focused to customer satisfaction, obtain some basic benefits, like the hospital's reputation is more positive in the eyes customers and the community and encourage the creation of customer loyalty which makes it possible for hospitals increase profits, harmoniously the relationship of the hospital to its customers and encourage everyone in the hospital to work with more goals well. Strategies of hospital marketing are needed to increase patient satisfaction. We use Systematic Review with PRISMA method retrieved from online database such as ProQuest, Wiley online, J Store, Sciencedirect and local journals (Portal Garuda, Jurnal Promkes) using a keyword “Strategy”, “Hospital Marketing”, “Marketing”, “Patient Satisfaction”, range years 2011-2018. The end of this search got 8 journals. Many challenges are faced in implementing hospital marketing programs, such as: challenges between patients and the community, among fellow medical personel, between organizations and external barriers from outside and inside the hospital environment. Many the contextual factors that are very important as a determinant of whether this hospital marketing program is successful or not. Improving services may not only increase the number of employees who are professionally competent, but also about service arrangements and attention to things that are valued by patients. Research shows that many strategies like internal marketing, marketing mix, learning organization, organizational commitment, education and training staff, feasible and strategic goals of hospital marketing, supportive policies and conducted business online via interactive e-health tools are facilitating strategies for implementation hospital marketing. Hospital promoting is not only a matter of marketing units. But it has become the responsibility of all hospitals from the highest level to the lowest level. Many strategies and ways in implementing hospital marketing and factors as the key to successful implementation. To realize a hospital marketing program as the main service at the hospital, a strategic plan that supports the program is needed such as media promotion, resources, methods used and funds.